Abiotic Stress in Plants Adaptations to Climate Change - Oliveira, Manuel; Fernandes-Silva, Anabela (IntechOpen, 2023)
How plants adapt to climate change is a complex and multifaceted process and understanding it requires a comprehensive knowledge of plant biology and ecology. Some of the most serious stresses that plants face include heat and water stress, soil degradation, and increased pests and diseases. Addressing these challenges is crucial to preserve lives and livelihoods and requires a combination of scientific research, technical innovations, and policy interventions to increase ecosystem resilience and sustainable agricultural practices. This book is a step in the right direction, as it provides a comprehensive overview of plant adaptation to abiotic stresses.